Keberadaan Undeclared Pre-Existing Conditions Dalam Hubungan Hukum Perasuransian Pasca-Putusan Mahkamah Konstitusi Nomor 83/PUU-XXII/2024 - Gunawan Widjaja; Songga Aurora Abadi; Novi Rizky Ramadhani (CV. ITTC INDONESIA, 2025)
The legal relation in insurance law, both in theory and in practice, has undergone changes following the Constitutional Court Decision Number 83/PUU-XXII/2024, which conditionally declared Article 251 of the Indonesian Commercial Code (KUHD) unconstitutional. The aforementioned decision has had significant implications, not only in practical terms for the insurance business practices in Indonesia but also indirectly by altering the foundational concept of contractual obligations as recognized within the Indonesian legal system. The existence of undeclared pre-existing conditions, which has long served as the basis for the annulment of health insurance contract, can no longer be used by insurance companies as grounds to terminate their coverage relationship with policyholders. This normative legal research will elaborate on the implications of the enforceability of Article 251 of the Commercial Code following the Constitutional Court Decision Number 83/PUU-XXII/2024. In practice, the Constitutional Court Decision Number 83/PUU-XXII/2024 has had a positive impact on the protection of health insurance policyholders' rights. However, it also gives rise to legal inconsistencies when confronted with the concept of contractual law as recognized in the Indonesian legal system.